Unravelling reservoir quality heterogeneity in mixed siliciclastic-carbonate deposits: An example from Miocene Red Sea rift, NW Saudi Arabia. (November 2022) - Hussain, Arif; Butt, Muhammad Naveed; Olariu, Cornel; Malik, Muhammad Hammad; Koeshidayatullah, Ardiansyah; Amao, Abduljamiu; Al-Ramadan, Khalid
Abstract: The Miocene, syn-rift mixed siliciclastic-carbonate strata has been a long sought-after reservoir objective in the Red Sea rift basins. Despite being viable prospects, their depositional architecture, mechanisms of siliciclastics and carbonate mixing, and fundamental controls on their reservoir quality remained elusive and enigmatic. In this study, we used sedimentological, petrographical and outcrop permeametry measurements to investigate the stratigraphic record and reservoir quality of mixed siliciclastic-carbonate deposits. The latter are preserved at the transition between non-marine Al-Wajh Formation and marine carbonates of the Musayr Formation in one of the Red sea rift basins, NW Saudi Arabia. Three major facies associations were identified using detailed logging facies analysis, including siliciclastic-rich, mixed siliciclastic-carbonate and carbonate-rich facies association. These facies associations, represent a basinward transition from dominantly non-marine alluvial fans, braided streams and shallow-water delta into an open marine carbonate ramp. The permeability of siliciclastic facies is orders of magnitude higher (average permeability = 1884 md) than mixed siliciclastic-carbonate (average permeability = 109 md) and carbonate (average permeability = 46 md) facies. Likewise, siliciclastic facies have higher porosity (average porosity = 17%) compared to mixed (average porosity = 7%), and carbonate (average porosity = 15%) deposits. Petrographic analysis suggests that permeability and porosity variation within these facies is due to textural and diagenetic differences. Outcrop based permeability correlation separated the studied deposits into reservoir (excellent or good) and non-reservoir (baffles or barriers) elements. The relatively thick (5–10 m) and laterally continuous (hundreds of meters) siliciclastic deposits form excellent and good reservoir compared to usually thinner (1–2 m) mixed siliciclastic-carbonate and carbonate beds, which may act as baffles and barriers. This reservoir-seal configuration highlights the potential of stratigraphic trap formation in analogous settings in the subsurface, where non-marine siliciclastic deposits show lateral transition to marine carbonates. Highlights: Mixed siliciclastic-carbonate interval identified at the contact between Al-Wajh siliciclastics and Musayr carbonates. Outcrop-based permeability measurements made for siliciclastic, mixed, and carbonate deposits. Siliciclastics have orders of magnitude higher permeability than mixed, and carbonate facies. Permeability heterogeneity linked to both textural and diagenetic differences between facies. Siliciclastics form excellent reservoirs whereas mixed, and carbonates act as baffles and barriers.